Production of polyhydroxyalkanoates (PHA) using sludge from different wastewater treatment processes and the potential for medical and pharmaceutical applications - Lam, Wai (Environmental technology, 2017)
In this study, seven strains of bacteria with polyhydroxyalkanoates (PHA)-producing ability (i.e. Bacillus cereus, Pseudomonas putida, Bacillus pumilus, Pseudomona huttiensis, Yersinia frederiksenii, Aeromonas ichthiosmia, and Sphingopyxis terrae) were isolated from various waste treatment plants in Hong Kong. Simultaneous wastewater treatment and PHA accumulation were successfully achieved in the bioreactors using isolated bacteria from different sludges. At the organic loading less than 13,000 ppm, more than 95% of chemical oxygen demand (COD) was removed by the isolated strains before the decrease of PHA accumulation. In addition, more than 95% of nitrogen removal was achieved by all isolated strains. In the bioreactors inoculated with single strains, the highest yields of poly(3-hydroxybutyrate) (PHB) and poly(3-hydroxyvalerate) (PHV) were obtained in A. ichthiosmia (84 mg PHB/g) and B. cereus (69 mg/g), respectively. For the mixed culture, the highest yields of PHB and PHV were increased by 55% and 45% in the system inoculated with B. pumilus and A. ichthiosmia. The biologically synthesized PHA also showed the potential applications in drug delivery and tissue engineering. PHA-nanoparticles loaded with pyrene were successfully prepared by recombinant Escherichia coli. The results of in vitro drug release and biocompatibility tests revealed that nanoparticles could be used as safer dray carriers with high loading capacity and efficiency. After 20 days, the cells successfully grew on 90% of the PHA-aortic valve